Characteristics of Corn Seed Sales in Hungary - Sedlák, Gergő (Acta Agraria Debreceniensis, 2003)
As seen on the above tables we can acknowledge the fact that the Hungarian corn seed market is very unique and, because of its size, indispensable for all multinational breeder companies. We can also assume that the main places in the market are taken by big companies as Pioneer, with its unbreakable first place, followed closely by Syngenta Seeds and the fusionized Monsanto. Although the Hungarian breeders’ hibrids perform on field tests and trials similarly or better than other varieties developed by the above mentioned companies, we can’t find them even near to those leading few given mostly by Pioneer, Syngenta and Monsanto hibrids. This fact leaves us with a conclusion that the Hungarian companies should change the strategy of their marketing procedures to increase sales.Thus, they need better technology to keep up with their competitors, more advertisement, other marketing „hints”, which can only be fulfilled with a big economical background, unfortunately not yet available for our breeders.